The testretest reliability of the Opiate Treatment Index in nyaope users in Johannesburg - Pitsoane, Kelebogile; Morgan, Nirvana; Mall, Sumaya (My University, 2025)
Background: Epidemiological studies suggest that nyaope, a heroin-based drug, is widely used in South Africa. Yet few reliable research tools are available to assess treatment outcomes of users. The Opiate Treatment Index (OTI), a tool developed in Australia, could potentially facilitate research on context-specific South African treatment outcomes. However, we know little of its test-retest reliability. Aim: This study aimed to assess the test-retest reliability of the OTI among a sample of nyaope users in Johannesburg. Setting: This study was conducted across three substance use treatment facilities in Johannesburg. Methods: The OTI was administered to 53 nyaope users at baseline and one week later. To determine the test-retest reliability of the OTI, the intra-class correlation coefficients (ICC) and the Brennan–Prediger coefficients of the two interviews were calculated. Results: The ICC of the Q-scores from the data sets along with the Brennan–Prediger coefficient for the substance use domain were calculated. The ICC for nyaope was 0.38. Brennan–Prediger coefficients were as follows: alcohol – 0.96, crack-cocaine – 0.89, cannabis – 0.92, methaqualone – 0.85 and crystal methamphetamine – 0.89. Conclusion: A significant positive finding was the excellent test-retest reliability of the injecting and sexual behaviour domains and moderate reliability of the criminality, general health and social functioning domains. Contribution: The results of this study provide insight into the reliability of this tool and for its use in future studies in the South African context.
Keywords: Nyaope; Opiates; Test -retest reliability; Opiate treatment index; Substance users opioids; Heroin; Rehabilitation; Johannesburg; SDG:3- Good health and well-being